Enchanted [videorecording (Blu-Ray + DVD)] - Josephson, Barry; Sonnenfeld, Barry; Kelly, Bill (Screenwriter); Lima, Kevin; Adams, Amy; Dempsey, Patrick, 1966-; Marsden, James, 1973-; Spall, Timothy, 1957-; Menzel, Idina; Sarandon, Susan, 1946- (Disney Blu-ray., 2011)
A princess is banished from a magical animated land and finds herself in modern-day Manhattan, where a cynical man comes to her rescue.